PENGERINGAN SUHU RENDAH DAN LABELING KEMASAN UNTUK BEE POLLEN: PEMBERDAYAAN KELOMPOK TANI RANGERS BEE, LUBUK GILANG - Anis, Ulfah; Andini, Vicka; Wulandari, Sri; Yuwita, Fitri; Renaningtias, Nurul (Universitas Mataram, 2025)
The Rangers Bee Farmers Group in Lubuk Gilang Village has utilized three local bee species; Apis cerana, Apis dorsata, and Trigona to increase farmers’ income through honey production. However, the potential of other bee products, such as bee pollen, has not been optimally developed. The farmers lack knowledge and skills in post-harvest processing, particularly in drying techniques and marketing strategies. As a result, bee pollen remains unprocessed and is discarded as waste. This community service activity aims to enhance participants’ knowledge of bee pollen nutrition and processing to improve product shelf life, introduce traditional and oven drying methods, and provide mentoring in bee pollen processing. The activity employed an experiential learning approach. It began with a lecture session conducted by the community service team on the nutritional value of bee pollen and the stages of bee pollen processing. This was followed by hands-on practice, where the team and participants collaboratively processed bee pollen using an oven dryer. Post-activity mentoring was also carried out to support the sustainability of the practice. The community service program in Lubuk Gilang Village was attended by members of the Rangers Bee Farmers Group and local residents. The program began with an educational session on the nutritional content of bee pollen and its role in maintaining human health. The team further explained the stages of bee pollen processing, including sorting and drying, with the target moisture content below 10%. Additionally, the team introduced proper packaging and labeling techniques and showcased examples of bee pollen products marketed through online platforms. Following the activity, the team continued mentoring sessions to assist the farmers in conducting independent drying experiments on their harvested bee pollen. The community service activity resulted in a 26.87% increase in the farmers’ and community members’ knowledge and understanding of bee pollen nutrition, processing techniques, and marketing, as measured through questionnaire assessments.